Adsorption characteristics and mechanism insights of manganese modified biochar for Pb (II) adsorption in wastewater - Ahmed, Waqas; Wang, Yunting; Ali, Sehrish; Núñez-Delgado, Avelino; Qin, Fengyue; Dong, Menglu; Li, Weidong; Mehmood, Sajid (Frontiers in Environmental Science, 2026)
The release of lead (Pb) from industrial sources into aquatic environments is a growing concern due to its toxic nature, persistence, and tendency to bioaccumulate, posing significant environmental and health threats. This research involved the synthesis of a manganese-modified bamboo biochar (Mn-BC) using KMnO4 impregnation, and its effectiveness in removing Pb(II) was assessed against that of unmodified biochar (BC). Characterization by SEM, TEM-EDS, XRD, BET, and XPS verified successful Mn integration, leading to surface structural changes, Mn-oxide formation, and increased porosity. Mn-BC exhibited a specific surface area of 121.28 m2 g-1 and a total pore volume of 0.062 cm3 g-1, surpassing the values for BC, thus offering more active sites for Pb(II) adsorption. Batch adsorption tests indicated that Mn-BC attained a maximum Pb(II) adsorption capacity of 153.63 mg g-1, which is nearly five times higher than that of BC (30.22 mg g-1). At an adsorbent application of 1 g L-1, Mn-BC removed over 90% of Pb(II) from the solution, while BC managed only about 30%. The adsorption kinetics were analyzed by using the pseudo first order (PFO), second order (PSO) and intraparticle diffusion kinetic models and were best described by the pseudo-second-order model (49 mg g-1 and R2 = 0.99), suggesting that chemisorption was the primary mechanism, with intraparticle diffusion playing a role. The equilibrium data conformed to the Langmuir isotherm (153.63 mg g-1 and R2 = 0.98), indicating monolayer adsorption on uniform active sites. Thermodynamic analysis showed negative energy values (ΔG°) ranging from −12.4 to −18.7 kJ mol-1, a positive enthalpy and entropy change (ΔH° and ΔS°), suggesting spontaneous adsorption process and endothermic in nature. Regeneration studies revealed that Mn-BC retained 79% of its initial adsorption capacity after five cycles, compared to 64% for BC, highlighting its superior stability and reusability. XPS analysis showed that Pb(II) was immobilized through complexation with oxygen-containing functional groups and Mn species. These results suggest that Mn-BC is a cheaper, stable, and eco-friendly adsorbent with considerable potential for large-scale treatment of Pb(II)-contaminated wastewater.